DOK7 Inhibits Cell Proliferation, Migration, and Invasion of Breast Cancer via the PI3K/PTEN/AKT Pathway - Yue, Changli (J Oncol, 2021)
Recently, increasing attention has been paid to the correlation between the expression of downstream of kinase 7 (DOK7) and the occurrence and development of various tumors. In this study, we clarified the effects of DOK7 in breast cancer. First, we showed that DOK7 expression was obviously reduced in the breast cancer tissues and lower levels of DOK7 linked to more aggressive behaviors and worse prognosis of patients. Furthermore, DOK7 expression of various breast cancer cell lines was lower than that of human noncancerous MCF-10A cells. Overexpression of DOK7 inhibited proliferation, migration, and invasion, while silencing DOK7 expression promoted the malignancy of breast cancer. In addition, overexpression of DOK7 suppressed tumor proliferation and lung metastasis in animal models. Finally, to investigate the possible signaling mechanism, we first found that the level of p-AKT protein was extremely downregulated and the level of PTEN protein was remarkably upregulated after overexpressing DOK7 in breast cancer cells. Repression of PTEN expression using PTEN siRNA or SF1670 (PTEN inhibitor) rescued the tumor-inhibiting effect induced by DOK7 overexpression, suggesting that DOK7 inhibits proliferation, migration, and invasion of breast cancer cells though the PI3K/PTEN/AKT pathway. These results suggest that the downregulation of DOK7 may become a novel breast cancer therapeutic target.